The Importance Of Literary Works An As Alternative To Spiritul Therapy In The Formation Of Soft Skills - Rosnani Ripin; Amrina Rasyada Kamaruzaman (Rabbanica: Journal of Revealed Knowledge)
Every individual now recognizes the importance of mental therapy in society, given the increasing prevalence of stress, mental illness, and suicide symptoms. Counseling sessions, motivation, and religious guidance conducted by certain parties are necessary, as are mental treatment efforts to support the integrity of a person's soul. This study identifies the attributes of sakinah (calmness) and its connection with the elements of soul therapy in characters in selected novels, namely Imam Markisa and Doa Insan Berkasih by Aminah Mokhtar. This study employs qualitative and literary methods, applies Takmilah Theory to both books, and demonstrates the elements of mental therapy derived from the discovery of the sakinah's qualities. The identification of soul therapy elements in the novels' characters has the potential to infuse the readership with a sense of spirituality. As a result, creative works with Islamic elements have become a necessity and are highly relevant to the primary reading material other than the Quran. Additionally, schools can use it as a literary component (Komsas).